2007
DOI: 10.1097/mpg.0b013e31802f6424
|View full text |Cite
|
Sign up to set email alerts
|

Hepatosplenic T Cell Lymphoma Associated With Infliximab Use in Young Patients Treated for Inflammatory Bowel Disease

Abstract: Hepatosplenic T cell lymphoma (HSTCL) are rare cancers ( approximately 100 published cases worldwide) and comprise 5% of peripheral T cell lymphomas. As of October 5, 2006, the FDA's Adverse Event Reporting System has received 8 cases of HSTCL in young patients using infliximab, a tumor necrosis factor-alpha blocking agent, to treat inflammatory bowel disease (6 of the 8 cases had a fatal outcome). All 8 patients were receiving concomitant immunosuppressant therapy (eg, azathioprine, prednisone). It has not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
255
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 447 publications
(271 citation statements)
references
References 6 publications
(7 reference statements)
4
255
0
9
Order By: Relevance
“…8 In the group of IBD patients, HSTCL has been described since 2007. 9 An international warning derived from the observation that IBD patients treated with anti-TNFs developed fatal HSTCL (especially young males). But as a result of recently published data regarding risk factors for HSTCL in patients with IBD that showed that most patients received a combination of thiopurines and anti-TNFs, the discussion emerged that not only are the anti-TNFs risk factors, but also thiopurines themselves or the combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…8 In the group of IBD patients, HSTCL has been described since 2007. 9 An international warning derived from the observation that IBD patients treated with anti-TNFs developed fatal HSTCL (especially young males). But as a result of recently published data regarding risk factors for HSTCL in patients with IBD that showed that most patients received a combination of thiopurines and anti-TNFs, the discussion emerged that not only are the anti-TNFs risk factors, but also thiopurines themselves or the combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphomas that have occurred during thiopurine therapy have increasingly been recognized to be related to Epstein -Barr infections (216,217,221) . A rare form of natural killer cell, hepatosplenic lymphoma has recently been described associated with azathioprine therapy for CD either alone (222) or in combination with in iximab (223,224) . Weekly methotrexate at a dose of 15 mg, intramuscularly, has also been demonstrated to maintain methotrexate-induced remissions (225) , but optimal dosing has not been established (15,17,226,227) .…”
Section: Maintenance Therapymentioning
confidence: 99%
“…The only exception is constituted by 8 cases of hepatosplenic  T-cell lymphoma diagnosed among young patients treated with infliximab or adalimumab for inflammatory bowel disease. All patients were receiving concomitant immunosuppressive therapy with azathioprine or prednisone and it was not possible to ascertain if anti-TNF medication had an exclusive role in the pathogenesis of these lymphomas (Mackey et al, 2007). Conversely, although it has not been definitively demonstrated, postponing therapy could contribute to lymphoma development; this could be due to a chronic worsening of the inflammatory microenvironment promoted by uncontrolled disease.…”
Section: Therapeutic Agentsmentioning
confidence: 99%